2002
DOI: 10.1046/j.1469-0691.2002.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin susceptibility of viridans streptococci from the normal throat flora of patients treated with azithromycin or clarithromycin

Abstract: There is a pool of streptococci carrying genes associated with macrolide resistance in the normal respiratory flora of generally healthy adults. Differences between the patients treated with clarithromycin and those treated with azithromycin were difficult to assess because of the large number of patients in each group with macrolide-resistant streptococci before treatment. Although there were some differences these were not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…MefA and mefE genes are no longer considered to be different and only mefA is described in [11]. Surveys from Spain [4] and the UK [12] indicated that among VGS strains isolated from patients suffering from pharyngitis and respiratory tract infections, the M phenotype and mefA gene presence predominated. However, another study from Spain [13] reported equal numbers of CR MLS B and M phenotypes, with different distributions being detected among the different species: the CR MLS B phenotype predominated in S. oralis and S. sanguis, whereas the M phenotype predominated in S. mitis and S. salivarius .…”
Section: Resultsmentioning
confidence: 99%
“…MefA and mefE genes are no longer considered to be different and only mefA is described in [11]. Surveys from Spain [4] and the UK [12] indicated that among VGS strains isolated from patients suffering from pharyngitis and respiratory tract infections, the M phenotype and mefA gene presence predominated. However, another study from Spain [13] reported equal numbers of CR MLS B and M phenotypes, with different distributions being detected among the different species: the CR MLS B phenotype predominated in S. oralis and S. sanguis, whereas the M phenotype predominated in S. mitis and S. salivarius .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies from different European countries similarly report the presence of macrolide-resistant viridans streptococci in healthy people [13,[15][16][17], mainly due to the presence of mef(A). However, these studies report much higher frequencies of the gene than found in our study, probably due to the differences in antimicrobial use between the countries [18].…”
Section: Discussionmentioning
confidence: 98%
“…In one study, macrolide administration was associated with high-level macrolide resistance 3 weeks (38% vs 55%, p = 0.02), but not 5-6 weeks (38% vs 41%, p = 0.8) after completing the course of therapy [9].…”
Section: Discussionmentioning
confidence: 99%